Physiotherapist's activity in range of motion in the post operation of anterior cruciated ligament (Research, Society and Development, 2023)
The Anterior Cruciate Ligament (ACL) is a complex structure essential for the stability of the knee, composed of the anteromedial and posterolateral bundles, they are frequently associated with sporting activities, they result from varied mechanisms, the most common being during changes of direction with the foot fixed and knee flexed. The severity of injuries is classified into grades 1, 2 and 3. Surgical reconstruction has become an option with innovative techniques, but the choice of treatment involves critical considerations such as the type of graft, single or double bundle reconstruction, location of the graft and surgical technique. The objective of this work is to show the importance of protection angles in total knee flexion and extension, tension suffered by the graft in open kinetic chain (CCA) and closed kinetic chain (CCF) exercises during treatment. This study reviews the literature between 2000 and 2022, highlighting the complexity of the knee joint, the anatomy of the ACL and the impacts of injuries to this ligament. A personalized physiotherapeutic approach is proposed, considering protection angles, graft tensioning in open and closed kinetic chain exercises. Injury prevention is addressed, emphasizing the importance of neuromuscular and functional training. Post-surgical rehabilitation is discussed, highlighting the relevance of isometric and functional exercises. Consideration of individual risk guides the choice between conservative treatment and reconstruction. The review emphasizes the need to understand the complex biomechanics of the knee joint and the importance of appropriate treatment to ensure health and functionality, especially in the context of ACL injuries.